Analysis of the Effectiveness of Existing Mechanisms of Governmental Support for Small Business in Russia ("Journal "U". Economy. Management. Finance.", 2018)
The article highlights the main features of small business, determines the criteria for assigning subjects to small businesses and the forms of governmental support for small enterprises, gives general information on interaction between the state and small business, analysis of their effectiveness and provides information about competitiveness of the Russian entrepreneurship.
Keywords: small business; small enterprise; government support of business; business competitiveness